(untitled) (TEL Tempo, Espaço e Linguagem, 2014)
Este artigo discute o lugar ocupado pelos Salesianos de Dom Bosco no processo “civilizatório” de Mato Grosso. Foi utilizada a literatura regional especializada, bem como as publicações da Missão Salesiana e arquivos disponíveis no NDHIR: Núcleo de Documentação Histórica e Regional, com sede na UFMT em Cuiabá. Abstract: This article discusses the place which the Salesians of Don Bosco occupied in the “civilizing” process of Mato Grosso. The following sources have been used: specialized regional literature, the Salesian Mission’s publications as well as the available archives at NDHIR: Historic and Regional Documentation Center, residing at UFMT in Cuiabá. Keywords: Salesians. Mato Grosso. Representations. Education. Resumen: Este artículo analiza el lugar ocupado por los Salesianos de Don Bosco en lo proceso de "civilizar" Mato Grosso. Se utilizó una literatura especializada regional, las publicaciones de la Misión Salesiana y archivos que se encuentran disponibles en NDHIR: Centro de Documentación Histórica y Regional, con sede en la UFMT en Cuiabá. Palabras clave: Salesianos. Mato Grosso. Representaciones. Educación.